Influence of pregnancy and labor on the occurrence of nerve fibers expressing the capsaicin receptor TRPV1 in human corpus and cervix uteri - Irestedt Lars; Facer Paul; Ekman-Ordeberg Gunvor; Tingåker Berith K; Anand Praveen (BMC, 2008)
Abstract Background Cervical ripening is a prerequisite for a normal obstetrical outcome. This process, including labor, is a painful event that shares features with inflammatory reactions where peripheral nociceptive pathways are involved. The capsaicin and heat receptor TRPV1 is a key molecule in sensory nerves involved in peripheral nociception, but little is known regarding its role in the pregnant uterus. Therefore, the aim of this study was to investigate human corpus and cervix uteri during pregnancy and labor and non-pregnant controls for the presence of TRPV1. Methods We have investigated human uterine corpus and cervix biopsies at term pregnancy and parturition. Biopsies were taken from the upper edge of the hysterotomy during caesarean section at term (n = 8), in labor (n = 8) and from the corresponding area in the non-pregnant uterus after hysterectomy (n = 8). Cervical biopsies were obtained transvaginally from the anterior cervical lip. Serial frozen sections were examined immunohistochemically using specific antibodies to TRPV1 and nerve markers (neurofilaments/peripherin). Results In cervix uteri, TRPV1-immunoreactive fibers were scattered throughout the stroma and around blood vessels, and appeared more frequent in the sub-epithelium. Counts of TRPV1-immunoreactive nerve fibers were not significantly different between the three groups. In contrast, few TRPV1-immunoreactive fibers were found in nerve fascicles in the non-pregnant corpus, and none in the pregnant corpus. Conclusion In this study, TRPV1 innervation in human uterus during pregnancy and labor is shown for the first time. During pregnancy and labor there was an almost complete disappearance of TRPV1 positive nerve fibers in the corpus. However, cervical innervation remained throughout pregnancy and labor. The difference in TRPV1 innervation between the corpus and the cervix is thus very marked. Our data suggest that TRPV1 may be involved in pain mechanisms associated with cervical ripening and labor. Furthermore, these data support the concept that cervix uteri may be the major site from which labor pain emanates. Our findings also support the possibility of developing alternative approaches to treat labor pain.